Marie Poussepin’s Influence on Nursing from Her Vocation of Service and Charity (2023)
Objective. This work sought to describe the influence of Marie Poussepin on Nursing from her vocation of service and charity. Method. Historical-hermeneutic study with participation by 15 Dominican Sisters of Charity in the Presentation of the Blessed Virgin from the city of Manizales and Bogotá, Colombia, who answered semistructured interviews. The information was gathered and recontextualized via the open and axial coding system through ATLAS.ti9 software. During the interpretation procedure, copying, intensive reading, note taking, analysis, first epigraph of the report, coding, grouping, and determination of categories was made, conducting information triangulation with existing evidence. Results. Three categories emerged: Responding to the call of Jesus through service to the community; Under the legacy of charity, respect for life and the dignity of human beings, and Caring for life as a foundation of nursing. The second category formulated the description that integrates the course of life and objectives of the institutions where the nuns interviewed work. Conclusion. The legacy by Marie Poussepin to nursing care has been manifested since the foundation of the work, influencing the disciplinary work through the vocational commitment of those who make up the congregation, imprinting a character of service and respect for others, in response to the love of God.